INCREASING KNOWLEDGE AND SKILLS IN THE EARLY DETECTION OF MENTAL DISORDERS THROUGH TRAINING MENTAL HEALTH CADRES AT CITY HEALTH CENTERS - Eka, Angelina Roida; R Iwa, Kornelia; Nursi Nggarang, Bonavantura; Handi, Heribertus (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Mental disorders are still a global concern, including in Indonesia. According to basic health research conducted by the Indonesian Ministry of Health, as much as 0.14% of Indonesia's population has severe mental disorders. This is mainly due to the lack of mental health services, especially in remote areas such as East Nusa Tenggara which have limited health services. The purpose of community service is to optimize the role of mental health cadres in community mental health programs by providing mental health cadre training so that cadres can carry out their roles which include primary, secondary, and tertiary prevention. This research method was carried out by providing educational training to mental health cadres. This training is expected to be able to help puskesmas increase the coverage and sustainability of mental health services to ODGJ by optimizing the role of the community, in this case, especially mental health cadres by carrying out early detection and mobilizing ODGJ and their families to carry out treatment so that there are no more ODGJ who are shackled but can instead recover and be productive.